Transcultural adaptation and validation of the Spanish version of the Global Pain Scale - Ortega-Ávila, Ana Belén; Gijón-Noguerón, Gabriel; Cervera-Garvi, Pablo; Guerra-Marmolejo, Cristina; Chicharro-Luna, Esther; Reinoso-Cobo, Andrés; Marchena-Rodríguez, Ana José (Wiley, 2022)
The aim of this study was to perform a cross-cultural adaption and validation of the Global Pain Scale (GPS) to produce a Spanish-language version (GPS-Sp) and to determine the psychometric properties of this instrument. The GPS was cross-culturally translated into Spanish following the guidelines of the International Society for Pharmacoeconomics and Outcomes Research. The initial study population was composed of 384 patients recruited from February to May 2021. All participants were aged at least 18 years and were currently experiencing pain. All gave signed informed consent to take part and completed the Brief Inventory-Sp and GPS-Spain questionnaires. Cronbach's ɑ and test/retest reliability values were calculated and floor/ceiling effects analyzed. Construct validity was assessed by confirmatory factor analysis (CFA). The 370 patients included in the final analysis presented the following characteristics: 36.2% were male and 63.8% were female; mean age 42.6 (19–88) years; mean body mass index 24.99. Internal consistency was good. The Cronbach's ɑ for GPS-Sp was 0.86 and the intraclass correlation coefficient was 0.94 (95% CI; 0.87–0.97). Five main explanatory factors were identified by CFA, which produced the following values: RMSEA = 0.057; CFI = 0.807; GFI = 0.809; NFI = 0.763. No floor/ceiling effect was observed. The GPS-Sp is a valid, reliable and sensitive instrument for assessing pain in a Spanish-speaking population and could facilitate pain relief in this population.
Keywords: Artrosis; Biomechanics; Clinical outcomes; Foot and ankle; Low back pain; Osteoarthritis